Pengaruh antara Tingkat Kepatuhan Orang Tua dalam Menjalankan Home Program dengan Kemampuan Pragmatik pada Anak ASD di PLDPI Kota Surakarta - Woro Setiadi, Elisa; Setyaningsih, Wiwik (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: The presence of parents as one of the components in society is one of the supporting components in the growth and development process of autistic children. Parental support becomes one of the factors for the success of therapies conducted by children, such as providing full support to the child, motivating the child, consulting about the child's issues, as well as parenting style. Regarding the pragmatic abilities of children with autism, they have difficulties in developing interactive conversations. This happens because the symptoms of autism make it difficult for them to understand and predict the thoughts and feelings of others. Objectives: This study aims to determine whether there is an Influence Between Parental Compliance Level in Conducting Home Programs and Pragmatic Abilities in Children with Autism Spectrum Disorder at PLDPI Surakarta City. Methods: This research is a quantitative study with an observational analytic research design, and the experimental design used is the One group pretest-posttest design. The sample size in this study is 30 autistic children at PLDPI Surakarta City using the Purposive Sampling technique. The statistical test used is Spearman rank.Results: The description of parental compliance in conducting home programs yielded highly compliant results from 17 respondents, compliant from 9 respondents, and less compliant from 4 respondents. The description of pragmatic abilities in autistic children yielded highly capable results from 6 respondents, capable from 9 respondents, and less capable from 15 respondents. The Spearman's rank correlation test results showed ρ = 0.000 (ρ < 0.05 = Ha accepted), with an r value of 0.619 and a positive correlation direction. Conclusion: Based on the analysis of the data, it can be concluded that there is an influence between the level of parental compliance in conducting home programs on pragmatic abilities in children with Autism Spectrum Disorder at PLDPI Surakarta City. The strength of the influence between these two variables falls into the strong category. Keywords: Level of Parental Compliance, Home Program, Pragmatic Ability, Children with Autism Spectrum Disorder